ENERGY SAVING THROUGH IMPROVED TOPOLOGY OF THE CITY WATER NETWORK - Novokhatniy, V.; Matyash О.; Usenko І. (Municipal economy of cities. Series: «Economy science», 2023)
This article compares the operation of the existing water supply system in the city Kremenchuk, Poltava region, namely the giving-distributive complex (GDC), which includes the main water network and the pumping station of the 2-nd lift, with the GDC, in which the topological structure has been improved by introducing a new section of the network. During the operation of the GDC, the tasks of repairing or replacing pipes of individual sections the water network constantly arise. At the same time, attention should also be paid to the topological structure of the water network during its reconstruction. The need to improve the topological structure is clearly seen after performing hydraulic calculations and building piezometric maps. For comparison, piezometric maps need to build before and after the reconstruction of the water network. At the nodal points of the network, a geodetic mark, free pressure and piezometric mark are shown. Considering that water moves from a larger piezometric mark to a smaller one, the directions of water movement and water network nodes with minimal free pressures are determined. At the same time, flaws in the topological structure are found on the piezomap, which should be eliminated in order to increase its dependebility. It is known that dependebility includes 3 components: reliability, maintainability and durability. Durability is ensured by the choice of pipe material during design. If we take into account simultaneously reliability and maintainability, then a complex indicator should be used, namely, the availability factor Ka. It estimates the probability that at any given time the section of water network is in working condition. According to the topological structure, the water network of the city should be looped and have more connections between nodes. But in practice, this principle can not always be maintained, given the planning structure of the streets the city. Graphical representation of hydraulic calculations using piezomaps allows you to identify overloaded sections of the water network and increase its dependebility. When improving the topological structure, it is necessary to use the prof. Novokhatniy principle, namely, new sections must be introduced so that they unite the existing nodes of the existing water network. Hydraulic calculations have shown that by improving the topological structure of the water network the city Kremenchuk, the annual energy saving is about 452 thousand kWh, which corresponds to a saving of about UAH 2.7 million per year (at the cost of electricity 6 UAH per 1 kWh).